2022
DOI: 10.1177/14759217211045912
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring deformations of infrastructure networks: A fully automated GIS integration and analysis of InSAR time-series

Abstract: Ageing stock and extreme weather events pose a threat to the safety of infrastructure networks. In most countries, funding allocated to infrastructure management is insufficient to perform systematic inspections over large transport networks. As a result, early signs of distress can develop unnoticed, potentially leading to catastrophic structural failures. Over the past 20 years, a wealth of literature has demonstrated the capability of satellite-based Synthetic Aperture Radar Interferometry (InSAR) to accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 122 publications
0
26
0
Order By: Relevance
“…Most of these studies have concentrated on cross validation of satellite-based monitoring through comparison with independent ground-based measurements for real case studies. Examples included buildings [275,276], railways [277], roadways [278,279], dams [280] and bridges [281,282]. An extensive literature review on MT-InSAR civil engineering application can be found in [279].…”
Section: Multi-temporal Interferometric Synthetic Aperture Radar (Sar...mentioning
confidence: 99%
“…Most of these studies have concentrated on cross validation of satellite-based monitoring through comparison with independent ground-based measurements for real case studies. Examples included buildings [275,276], railways [277], roadways [278,279], dams [280] and bridges [281,282]. An extensive literature review on MT-InSAR civil engineering application can be found in [279].…”
Section: Multi-temporal Interferometric Synthetic Aperture Radar (Sar...mentioning
confidence: 99%
“…The most updated works are focusing on developing sophisticated infrastructure monitoring approaches using interferometric measurements along with GIS and/or machine learning algorithms such as regression tree, support vector machine, boosted regression trees, random forest, etc. [29,30]. These newly developed methods are able to provide: a) full automation of deformation detection and/or the extraction of possible warnings and b) effective decision-making tools.…”
Section: Introductionmentioning
confidence: 99%
“…Macchiarulo V et al proposed a method based on the full integration of MT-InSAR data and GIS-based analysis. By automatically processing a large number of PS displacement time series and road network databases, they obtained a localized deformation analysis of abnormal differential motion between different parts of the same infrastructure [7] . Zhao Fumeng et al conducted research on the geological disaster deformation characteristics along the China-Pakistan Highway (Chinese section), the vulnerability assessment of developed landslide disasters, and the relationship between the distribution patterns of geological disasters and various environmental factors [8] .…”
Section: Introductionmentioning
confidence: 99%